Fungal diseases and their effect on phytochemical constituents of medicinally important Terminalia species in Bhadra Wildlife Sanctuary, Karnataka, India - G.E. MALLIKARJUNASWAMY, M.B. SHIVANNA* and (Indian Phytopathology, 2009)
An investigation, during 2001-2003, on the foliar diseases of Terminalia species like T. arjuna, T. Bellirica ,T. chebula, T. paniculata and T. tomentosa in certain areas of Bhadra Wildlife Sanctuary revealed the association of the several fungal species with disease symptoms. Phoma herbarum in case of T. arjunaand T. paniculata, Colletotrichum dematium in T. bellirica,Macrophomina phaseolina in T. tomentosa and Pestalotiopsis versicolor in T. chebula were recorded pathogenic and also were found to produce symptoms of disease through out the year. Maximum disease incidence was recorded during the rainy season. On quantitative estimation a drastic decrease in alkaloid and steroid contents in diseased leaves was noticed. On the other hand, flavonoid and phenolic contents increased significantly in diseased leaves of most tree species understudy.